Sub Specie Aeternitatis. An Actualisation of Wittgenstein on Ethics and Aesthetics - Varga, Somogy (The Nordic Journal of Aesthetics, 2010)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif]–> <!–[endif]–> This article will present an interpretation of Wittgenstein’s understanding of the relationship between ethics and aesthetics. In extension, it will inform recent discussions regarding a special kind of nonsensicality, which forms a central part of ethical and aesthetical expressions. Instead of identity between ethics and aesthetics, we should understand the relationship in terms of interdependence. Both attitudes provide a view sub specie aeternitatis and thus permit a view of the world as a whole. Employing the vocabulary of Charles Taylor and Harry Frankfurt, it must be remembered that rather than a neutral view from nowhere, such wholeness arises out of strong evaluations that are made against the backdrop of a constitutive framework of intelligibility. At this point, the epistemic gain of actualizing Wittgenstein will reveal itself: it will put us in a position where it is possible to differentiate between ethical and aesthetical forms of identification that Taylor and Frankfurt neglect. However, in order to actualize Wittgenstein’s ideas, it is necessary to argue that Tractatus should not be understood in a Kantian fashion as suggested by Tilghman for instance.